Muscovite based polyaniline nanocomposite as effective adsorbent for removal of Cd2+ and Pb2+ ions from liquid waste - M. Nageeb Rashed; A. S. A. Arifien; F. A. El-Dowy (Scientific Reports)
Abstract Heavy metals in wastewater represent a main source of environmental contamination for the ecosystem and aquatic system. Herein, the in situ polymerization method was used to prepare a novel nanocomposite polyaniline/muscovite (PANI/Msc) using ammonium persulphate as an oxidizing agent and HCl as a catalyst. The combination of muscovite with polyaniline (PANI) creates a hybrid material that leverages the strengths of both components. PANI/Msc nanocomposite was characterized using XRD, TEM, FT-IR, SEM, and surface area analyzer. Crystalline size of the prepared nanocomposite found in the range 15.6 – 45 nm , while its surface area was 208.6 m2/g. The resulting nanocomposite was used for Cd2+ and Pb2+ adsorption from their solution. Up to 75.6 and 72.6% of Cd2+ and Pb2+, respectively, were removed in the optimized conditions of metal concentration 75 ppm, pH 6 and 7 for Pb2+ and Cd2+, adsorbent dose 0.1 g, 25 °C solution temperature, and 60 min contact time. Kinetic and adsorption studies clearly demonstrated that the results of the adsorption process followed the pseudo-second order (qe 32.8 and 33.1 mg g−1) and Langmuir models (Q0 36.1 and 61 mg g−1) for Cd2+ and Pb2+, respectively. The thermodynamic indicated favorable, spontaneous and exothermic process. Electrostatic interaction and ion exchange mechanisms were responsible for the adsorption of Cd2+ and Pb2+ by PANI/Msc as demonstrated by FTIR spectroscopy and pH studies. This study ended with the cost- effective preparation of PANI/Msc nanocomposite that offers a promising solution for the removal of heavy metals from contaminated water source. In addition, the capability study regarding Pb2+ and Cd2+ion adsorption over the PANI/Msc nanocomposite clearly revealed that our method is suitable for large- scale application.